Two new species of Promalactis and one newly recorded from Japan (Lepidoptera, Oecophoridae) - Tomura, Shunsuke; Komatsu, Toshitami; Yagi, Sadahisa; Hirowatari, Toshiya (Zootaxa, 2021)
Two new species of the genus Promalactis Meyrick (Lepidoptera: Oecophoridae) are described from Japan: P. inokoi Tomura & Komatsu sp. nov. and P. kogii Tomura, Yagi & Hirowatari sp. nov. Additionally, Promalactis hoenei Lvovsky, 2000, originally described from China is newly recorded from Japan. Images of the imagoes and male and female genitalia are provided.